Species identification of dried scallop adductor muscle (yao zhu) products sold on the market. (January 2017) - Wen, Jing; Zeng, Ling; Chen, Ziming; Zhou, Yi; Xu, Youhou; Chen, Daohai; Sun, Yulin; Zhao, Juan; Zhang, Wei; Li, Haipeng
Abstract: Dried scallop adductor muscle, known as yao zhu, has been ranked in the list of the eight sea treasures in Chinese cuisine, it has been commonly recommended and consumed in China over many centuries due to its delicious taste and abundant nutrition. However, the true species composition of the dried scallop adductor muscles in the trade is unclear. Indeed, it is difficult to identify the scallop species just based on their morphological characters of processed adductor muscles. In this study, 60 yao zhu products commercialized in Chinese market were analyzed in order to authenticate species. Direct sequencing and BLAST method based on a fragment of the 16S rRNA gene were carried out and results showed that 34 products (56.7%) were scallop species Argopecten irradians, and other 26 products (43.3%) were the scallop species Mizuhopecten yessoensis, indicated the yao zhu market were dominated by the both species, which were the introduced aquaculture scallop species. Moreover, a simple and fast PCR method proved to be capable of unequivocal identification between the two species. Therefore, this work facilitates the identification of yao zhu products in the market, support of food control and protection of consumers' rights. Highlights: Identification of the dried scallop adductor muscle product has been carried out. Market was dominated by Argopecten irradians and Mizuhopecten yessoensis. A simple PCR method proved to be capable of identification between the two species.